(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the radiological and functional outcome of induced membrane technique for the treatment of long bone defect due to post traumatic osteomyelitis. Methods: This descriptive study was conducted in Unit I Department of Orthopedic Surgery Jinnah Hospital Lahore. The study extended from 16th November 2018 to 15th May 2022.All patients with long bone post traumatic osteomyelitis with bone defects fulfilling the inclusion criteria were treated with induced membrane technique for eradication of infection followed by fixation and bone grafting. Follow up visits were scheduled for assessment of radiological and clinical union of fracture. Results: A total of 80 patients were included in this study. The mean age was 38.4±12.1 years. Male patients were 73 (91.3%) and females were 7 (8.7%). Right side was involved in 42(52.5%) patients and left side in 38(47.5%) patients. Tibia was involved in 63(78.7%) patients and femur in 17(21.2%) patients. Radiological and clinical union was achieved in 78(97.5%) patients. Conclusion: Induced membrane technique for long bone defect due to post traumatic Osteomyelitis resulted in higher union rates. This technique is therefore recommended as treatment of choice for long bone defect due to post-traumatic Osteomyelitis.